Enhancement of Nursing Innovators among Nursing Students in Public Higher Education Institutions - Umasawan Chooha,; Sipapa Pummarak,; Yupa Phopa,; Apinya Pianpijarn, (Journal of Educational Issues, 2024)
Nursing innovators are people with the ability to create beneficial health innovations. Consequently, developing nursing students to create innovative learning processes alongside the development of professional nursing skills is important. The purpose of this study was to determine the efficacy of an activity package in developing nursing innovators among nursing students in public higher education institutions. This quasi-experimental study was conducted at Rajamangala University of Technology Thanyaburi, Thailand, 2021. Thirty third-year undergraduate nursing students were randomly assigned to one group. The activity package based on design thinking model. Data were collected before, immediately after, and eight weeks after the intervention using “innovative knowledge” and “nursing innovative skills” questionnaires. The descriptive statistics, paired t-test, and analysis of variances with repeated measures were used to analyze the data in this study. The mean score of knowledge was significantly higher post-training (10.66±1.88 vs. 16.93±1.25, P = .000). The mean score for nursing innovative skills was significantly higher before, immediately after, and eight weeks after the intervention. Nursing innovator skills can be developed by using an activity package to encourage nursing students to engage in innovative learning processes while also developing professional nursing skills. Administrators of academic facilities should set guidelines for organizing training activities with the aim of building nursing innovation for nursing students.